2001
DOI: 10.5326/15473317-37-3-263
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and interobserver measurement variability of tibial plateau slope from lateral radiographs in dogs

Abstract: Measurement of the tibial plateau slope from lateral hind-limb radiographs is a preoperative requirement when performing tibial plateau leveling osteotomy (TPLO) for repair of the cruciate-deficient stifle in dogs. Two measurements of the tibial plateau slope in 312 stifles of 156 dogs were taken from lateral radiographs by each of three observers with varying degrees of experience in the measurement method. Intraobserver variability was +/-3.4 degrees, and interobserver variability was +/-4.8 degrees. No sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
138
7
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(164 citation statements)
references
References 0 publications
11
138
7
8
Order By: Relevance
“…The interobserver and intraobserver variability for lateral radiographs were described with typical errors of 1.0°and 0.9°for the medial plateau, respectively [23]. We question whether such a small difference is relevant regarding the broad range of PTS variability reported in the literature [8,11,12,20,25,26,34,35,46,47], particularly regarding the fact that Todd et al found only females to have different values from the control group [47]. Although some studies relied on the use of the medial PTS, Stijak et al [46] focused on the lateral PTS and reported only a greater lateral PTS promotes injury.…”
Section: Discussionmentioning
confidence: 94%
“…The interobserver and intraobserver variability for lateral radiographs were described with typical errors of 1.0°and 0.9°for the medial plateau, respectively [23]. We question whether such a small difference is relevant regarding the broad range of PTS variability reported in the literature [8,11,12,20,25,26,34,35,46,47], particularly regarding the fact that Todd et al found only females to have different values from the control group [47]. Although some studies relied on the use of the medial PTS, Stijak et al [46] focused on the lateral PTS and reported only a greater lateral PTS promotes injury.…”
Section: Discussionmentioning
confidence: 94%
“…Ostatnie doniesienia wskazują, że kąt zgięcia stawu kolanowego nie ma wpływu na wartość mierzonego TPA (4). Wykorzystywano różne miejsca padania wiązki centralnej promieniowania X. Umieszczano ją na środku trzonu kości piszczelowej (13,40), w innych kierowano promieniowanie na staw kolanowy (6,47,49,65). Reif i wsp.…”
unclassified
“…Przebiega ona przez doczaszkową granicę plateau kości, będącą miejscem przyczepu więzadła krzyżowego doczaszkowego (6,13,15,21,40,42,47,48,60,65) oraz w części doogonowej przez miejsce przyczepu więzadła krzyżowego doogonowego. Doogonowy punkt wyznaczano również w miejscu głowy kości strzałkowej (46, 66) lub najbardziej wysuniętej doogonowo części przyśrodkowego kłykcia kości piszczelowej (1).…”
unclassified
See 2 more Smart Citations